Skeletal muscles and gut microbiota-derived metabolites: novel modulators of adipocyte thermogenesis - Tang, Yi; Wang, Ya-Di; Wang, Yuan-Yuan; Liao, Zhe-Zhen; Xiao, Xin-Hua (Frontiers in Endocrinology, 2023)
Obesity occurs when overall energy intake surpasses energy expenditure. White adipose tissue is an energy storage site, whereas brown and beige adipose tissues catabolize stored energy to generate heat, which protects against obesity and obesity-associated metabolic disorders. Metabolites are substrates in metabolic reactions that act as signaling molecules, mediating communication between metabolic sites (i.e., adipose tissue, skeletal muscle, and gut microbiota). Although the effects of metabolites from peripheral organs on adipose tissue have been extensively studied, their role in regulating adipocyte thermogenesis requires further investigation. Skeletal muscles and intestinal microorganisms are important metabolic sites in the body, and their metabolites play an important role in obesity. In this review, we consolidated the latest research on skeletal muscles and gut microbiota-derived metabolites that potentially promote adipocyte thermogenesis. Skeletal muscles can release lactate, kynurenic acid, inosine, and β-aminoisobutyric acid, whereas the gut secretes bile acids, butyrate, succinate, cinnabarinic acid, urolithin A, and asparagine. These metabolites function as signaling molecules by interacting with membrane receptors or controlling intracellular enzyme activity. The mechanisms underlying the reciprocal exchange of metabolites between the adipose tissue and other metabolic organs will be a focal point in future studies on obesity. Furthermore, understanding how metabolites regulate adipocyte thermogenesis will provide a basis for establishing new therapeutic targets for obesity.